Potential autotrophic carbon-fixer and Fe(II)-oxidizer Alcanivorax sp. MM125-6 isolated from Wocan hydrothermal field - Wei, Mingcong; Zeng, Xiang; Han, Xiqiu; Shao, Zongze; Xie, Qian; Dong, Chuanqi; Wang, Yejian; Qiu, Zhongyan (Frontiers in Microbiology, 2022)
The genus Alcanivorax is common in various marine environments, including in hydrothermal fields. They were previously recognized as obligate hydrocarbonoclastic bacteria, but their potential for autotrophic carbon fixation and Fe(II)-oxidation remains largely elusive. In this study, an in situ enrichment experiment was performed using a hydrothermal massive sulfide slab deployed 300 m away from the Wocan hydrothermal vent. Furthermore, the biofilms on the surface of the slab were used as an inoculum, with hydrothermal massive sulfide powder from the same vent as an energy source, to enrich the potential iron oxidizer in the laboratory. Three dominant bacterial families, Alcanivoraceae, Pseudomonadaceae, and Rhizobiaceae, were enriched in the medium with hydrothermal massive sulfides. Subsequently, strain Alcanivorax sp. MM125-6 was isolated from the enrichment culture. It belongs to the genus Alcanivorax and is closely related to Alcanivorax profundimaris ST75FaO-1T (98.9% sequence similarity) indicated by a phylogenetic analysis based on 16S rRNA gene sequences. Autotrophic growth experiments on strain MM125-6 revealed that the cell concentrations were increased from an initial 7.5 × 105 cells/ml to 3.13 × 108 cells/ml after 10 days, and that the δ13CVPDB in the cell biomass was also increased from 234.25‰ on day 2 to gradually 345.66 ‰ on day 10. The gradient tube incubation showed that bands of iron oxides and cells formed approximately 1 and 1.5 cm, respectively, below the air-agarose medium interface. In addition, the SEM-EDS data demonstrated that it can also secrete acidic exopolysaccharides and adhere to the surface of sulfide minerals to oxidize Fe(II) with NaHCO3 as the sole carbon source, which accelerates hydrothermal massive sulfide dissolution. These results support the conclusion that strain MM125-6 is capable of autotrophic carbon fixation and Fe(II) oxidization chemoautotrophically. This study expands our understanding of the metabolic versatility of the Alcanivorax genus as well as their important role(s) in coupling hydrothermal massive sulfide weathering and iron and carbon cycles in hydrothermal fields.